Synthesis and Characterization of Novel Polyimide/SiO2 Nanocomposite Materials Containing Phenylphosphine Oxide via Sol-Gel Technique - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY, 2010)
In this article, a series of novel polyimide/silica (PI/SiO2) nanocomposite coating materials were prepared from tetraethoxysilane (TEOS), gamma-glycidyloxypropyl-trimethoxysilane (GOTMS), and polyamic acid (PAA) via sol-gel technique. PAA was prepared by the reaction of 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA) and bis (3-aminophenyl) phenyphosphine oxide (BAPPO) in N-methyl-2- pyrrolidone (NMP). BAPPO was synthesized hydrogenation of bis (3-nitrophenyl) phenyphosphine oxide (BNPPO) in the presence of Pd/C. The silica content in the hybrid coating materials was varied from 0 to 20 wt %. The molecular structures of the composite materials were analyzed by means of FF-IR and Si-29-NMR spectroscopy techniques. The physical and mechanical properties of the nanocomposites were evaluated by various techniques such as, hardness, contact angle, and optical transmission and tensile tests. These measurements revealed that all the properties of the nanocomposite coatings were improved noticeable, by the addition of sol-gel precursor into the coating formulation. Thermogravimetric analysis showed that the incorporation of sol-gel precursor into the polyimide matrix leads to an enhancement in the thermal stability and also flame resistance properties of the coating material. The surface morphology of the hybrid coating was characterized by scanning electron microscopy (SEM). SEM studies indicated that nanometer-scaled inorganic particles were homogenously dispersed throughout the polyimide matrix (C) 2009 Wiley Periodicals, Inc. J AppI Polym Sci 115: 3256-3264, 2010
Keywords: coatings; flame retardance; nanocomposite; polyimides; thin films; SILICA HYBRID FILMS; PHOSPHINE OXIDE